A Bayesian framework for object recognition under severe occlusion - GUERRERO PEÑA, Fidel Alejandro (2017)
PEÑA, Fidel Alejandro Guerrero também é conhecido em citações bibliográficas por: GUERRERO-PEÑA, Fidel Alejandro